Enhanced ionic conductivity in poly(vinylidene fluoride) electrospun separator membranes blended with different ionic liquids for lithium ion batteries - Barbosa, J. C. (2021)
Electrospun poly(vinylidene fluoride) (PVDF) fiber membranes doped with different ionic liquids (ILs) and sharing the same anion were produced and their potential as separator membranes for battery applications was evaluated. Different types of ILs containing the same anion, bis(trifluoromethylsulfonyl)im ide [TFSI] , were used with IL concentrations ranging between 0 and 15 wt% The morphology, microstructure, thermal and electrical properties (ionic conductivity and electrochemical window) of the membranes were evaluated. The presence of ILs in the PVDF polymer matrix influences the fiber diameter and the content of the polar 13 phase within the polymer, as well as the degree of crystallinity. The thermal stability of the membranes decreases with the incorporation of IL. Impedance spectroscopy tests show a maximum ionic conductivity of 2.8 mS.cm(-1) for 15% of 1-ethyl-3-methylimidazolium bis(tri fluoromethylsulfonyl)imide ([Emim][TFSI]) at room temperature. The electrochemical stability of the samples ranges from 0.0 to 6.0 V. When evaluated as battery separator membranes in C-LiFePO4 halfcells, a maximum discharge capacity of 119 mAh.g(-1) at C-rate was obtained for the PVDF membrane with 15% [Emim][TFSI], with a coulombic efficiency close to 100%. The results demonstrate that the produced electrospun membranes are suitable for applications as separators for lithium ion batteries (LIBs).